Neonatal Nurses Knowledge and Attitude toward Kangaroo Mother Care Practice - Ahmad, Anna (Latakia University Journal -Medical Sciences Series, 2020)
Background: kangaroo mother care (KMC): is a technique of newborn care where baby are kept skin-to-skin contact with mother. It is most commonly used for low birth-weight preterm babies, who are more likely to suffer from hypothermia, while admitted to a neonatal unit to keep the baby warm and support early breastfeeding. Purpose of this study was to find out neonatal nurses knowledge and attitude towards KMC practice in pediatric hospital. Methods: this descriptive study was carried out in neonatal intensive care unit in pediatric hospital in Lattakia. On A convenient sample of 30 nurses. Results: Most of nurses in this study (56.6%) had diploma degree, and (66.6%) of them had more than 6 years of experience. The majority of neonatal nurses (90%) have poor knowledge on KMC definition and benefits. The majority of studied nurses (93.3%) had negative attitude toward KMC practice, while very low percent (6.7%) had neutral attitude. Conclusion: Most of neonatal nurses had low level of knowledge on KMC, and the majority of them had negative attitude toward KMC. مقدمة: رعاية أم الكنغر (KMC): هي تقنية لرعاية الأطفال حديثي الولادة, يتم فيها إبقاء الطفل على اتصال جلد-جلد مع الأم. وتستخدم بشكل شائع للأطفال الخدج منخفضي الوزن عند الولادة، والذين هم أكثر عرضة لانخفاض حرارة الجسم، حيث يتم قبولهم في وحدة الأطفال حديثي الولادة للحفاظ على دفء الطفل ودعم الرضاعة الطبيعية المبكرة. كان الغرض من هذه الدراسة هو التعرف على مستوى معلومات ممرضات حديثي الولادة واتجاهاتهم حول ممارسة KMC في مستشفى الأطفال. المنهجية: أجريت هذه الدراسة الوصفية في وحدة العناية المركزة لحديثي الولادة في مستشفى الأطفال في اللاذقية على عينة متاحة من 30 ممرضة. النتائج: حصلت معظم ممرضات حديثي الولادة في هذه الدراسة (56.6%) على درجة الدبلوم، وكان (66.6%) لديهن أكثر من 6 سنوات خبرة. ولدى غالبيتهن (90%) معرفة ضعيفة حول تعريف وفوائد KMC. كما كان لدى غالبيتهن (93.3%) موقف سلبي تجاه ممارسة KMC، في حين أن نسبة منخفضة للغاية (6.7%) كان لديهن موقف محايد. الخلاصة: كان لدى معظم الممرضات حديثي الولادة مستوى معلومات منخفض حول KMC، وكان لمعظمهن موقف سلبي تجاه KMC.